Threonine Requirement of Broiler from 22-42 Days - Ayasan, Tugay; Okan, Ferda; Hizli, Hatice (International Journal of Poultry Science, 2009)
Threonine is considered to be the third limiting amino acid for broiler chicks fed low protein corn-soybean meal diets. Very limited information is available on the requirement of the threonine for broilers. The aim of this study was to determine the threonine requirements of broiler chickens from 22-42 days of age. Seventy five Ross 308 one-day-old male broiler chicks were divided into five dietary treatment groups of similar mean weight, comprising 15 birds each. They were fed a basal starting diet containing 23% CP, 3200 ME kcal/kg, 0.81% threonine and 1.24% lysine for first 3 weeks. Chicks were randomly assigned to five treatments involving 0.70, 0.75, 0.80, 0.85 and 0.90% of total threonine for 21 days (between 22-42 days). Results indicated that a linear response to dietary threonine for final body weight, body weight gain and threonine intake occurred in experiment but other live performance parameters were not impacted by dietary threonine. Our results suggest that the current NRC recommendation of 0.74% threonine for 3-6 week old broilers is adequate to support comparable growth performance.